Introducing global Englishes - Galloway, Nicola
"Introducing Global Englishes provides comprehensive coverage of relevant research in the fields of World Englishes, English as a Lingua Franca, and English as an International Language. The book introduces students to the current sociolinguistic uses of the English language, using a range of engaging and accessible examples from newspapers (Observer, Independent, Wall Street Journal), advertisements, and television shows. The book :Explains key concepts connected to the historical and contemporary spread of English.Explores the social, economic, educational, and political implications of Englishs rise as a world language.Includes comprehensive classroom-based activities, case studies, research tasks, assessment prompts, and extensive online resources.Introducing Global Englishes is essential reading for undergraduate and postgraduate students of applied linguistics, TESOL, and other related disciplines"--